Synthesis of spherical and rods-like titanium oxide nanoparticles (TiO2 NPs) and evaluation of their cytotoxicity towards colon cells in vitro - Klebowski, Bartosz; Kosinska, Karolina; Bukowska, Agnieszka; Zieliński, Piotr M.; Parlinska-Wojtan, Magdalena; Depciuch, Joanna (Biochimica et biophysica acta. General subjects, 2025)
Titanium oxide nanoparticles (TiO2 NPs) are currently used as ingredients in medicines and sunscreens. Unfortunately, recent information about TiO2 NPs indicates their undesirable biological effect on colon cells. Therefore, the aim of this work was to synthesize and evaluate the physicochemical characterization of spherical (TiO2 NSs) and rods-like (TiO2 NRs) NPs, followed by assessment their cytotoxicity. For this purpose, both normal colon epithelial cells (CRL-1790) and cancerous colon cells (SW480) were used. Scanning transmission electron microscopy (STEM) showed that TiO2 NSs with a diameter of ≈10 nm and TiO2 NRs with the size of the longer axis ≈25 nm and shorter axis ≈3 nm were obtained. Based on the selected area electron diffraction (SAED) patterns, it was found that crystalline phases were obtained for both TiO2 NPs. The UV–Vis spectra showed no contamination of TiO2 NPs. Zeta potential values were 9.7 mV and 3.1 mV for NSs and NRs, respectively. Cytotoxicity of TiO2 NPs was assessed using the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxy-methoxy-phenyl)-2-(4-sulfophenyl)-2H-tetrazolium) test for various concentration of NPs. The cytotoxic effect for both TiO2 NPs was visible for concentration of 75 μg/ml (for CRL-1790) and 50 μg/ml (for SW480) and higher, and it did not depend on the shape. Moreover, both types of TiO2 NPs (in higher concentration) induce the generation of reactive oxygen species (ROS) in cells cultured with these NPs. Holotomographic microscopy studies showed increased cellular uptake of TiO2 NPs by SW480. The obtained results for the synthesized TiO2 NPs are a promising prospect for their use in biomedical application. •Spherical (TiO2 NSs) and rod-like (TiO2 NRs) titanium oxide nanoparticles were obtained.•Both types of TiO2 NPs have a stronger cytotoxic effect on cancer SW480 cells than on normal CRL-1790 cells.•The cytotoxic effect does not depend on TiO2 NPs shape.•Possible use of these TiO2 NPs in biomedical applications.